PENGARUH DANA ALOKASI UMUM, DANA ALOKASI KHUSUS DAN DANA BAGI HASIL TERHADAP BELANJA MODAL DI KABUPATEN/KOTA PROVINSI JAWA TENGAH - Rustiana Marheni; Eko Triyanto (Jurnal Cakrawala Ilmiah, 2023)
This study aims to determine the effect of the General Allocation Fund (DAU), Special Allocation Fund (DAK) and Revenue Sharing Fund (DBH) to the capital expenditures. The population in this study were 35 Cities/Regencies in Central Java in 2016-2020. The data used in this study is from the Realization Report of the Regional Revenue and Expenditure Budget (LRAPBD) which is accessed through the official website of the directorate general of financial balance in the City/Regency in Central Java. The method of data analysis in this study used multiple linear regression analysis. The results showed that general allocation funds, special allocation funds and profit-sharing funds partially or simultaneously had significant results on capital expenditures in cities/districts in Central Java.